Encyclopedias about Muslim civilisations - Khanbaghi, Aptin (Muslim civilisations abstracts., 2009)
Established in London in 2002, the Aga Khan University, Institute for the Study of Muslim Civilisations aims to strengthen research and teaching about the heritages of Muslim societies as they have evolved over time, and to examine the challenges these societies face in today's globalised world. It also seeks to create opportunities for interaction among academics, traditionally trained scholars, innovative thinkers and leaders, in an effort to promote dialogue and build bridges.